GIS-based mapping of illegal waste disposal sites to support waste management in Alam Barajo subdistrict - Rahmat, Andree Aulia; Wulansari, Arnati; Rahim, Beny; Hidayat, Ahmad Thohir; Ridhoka, M. Berri (Proceedings Academic Universitas Jambi, 2025)
Background: llegal waste disposal sites are an environmental problem that affects public health and the aesthetics of urban areas. Objective: This study aims to map the locations of illegal waste disposal sites in Alam Barajo District, Jambi City, and analyze the factors that influence their existence. Methods: The research method uses a descriptive approach with field survey techniques, direct observation, and geographical coordinate documentation using GPS. The data is analyzed with the help of a Geographic Information System (GIS) to visualize the distribution of illegal waste disposal sites. Results: The results of the study show that there are 10 points of illegal waste disposal site distribution that are almost evenly spread across 7 villages in Alam Barajo Subdistrict, namely 1 point in Kenali Besar Village, 1 point in Rawasari Village, 6 points in Pinang Merah Village, 1 point in Simpang Rimbo Village, and 1 point in Mayang Village. Most (70%) illegal waste disposal sites are located on neighborhood roads. Thus, the existence of these illegal waste disposal sites has a high potential to pollute the environment because they are located close to residential areas. Conclusion: This study recommends the need to add official waste collection sites from the Environmental Agency or from existing waste managers in the sub-district that are evenly distributed, increase public awareness about waste management, and consistently enforce environmental regulations to reduce the existence of illegal waste collection sites in the Alam Barajo sub-district.